Sprint Acceleration and Two-Leg Skipping: Methods for Improve Football Dribbling Ability - I Ketut Sudiana; I Gede Suwiwa; Gede Eka Budi Dharmawan; Gede Doddy Tisna; Gede Mardana; Ketut Chandra Adinata Kusuma (Universitas Pendidikan Ganesha, 2023)
Dribbling the ball is one of the basic techniques that football players must master. It is just that not all students can master the basic techniques of dribbling properly due to the lack of training given by the coach. One of the exercises that can improve the ability to dribble is the sprint acceleration exercise and two-leg skipping. This study aims to reveal the effect of sprint acceleration training and two-leg skipping on the ability to dribble the ball. This research belongs to the type of quasi-experimental research (quasi-experimental). The population in this study was all high school students. Sampling in the study was conducted using a random sampling technique to obtain the research sample of as many as 30 students who participated in extracurricular football. Data collection in this study was carried out using the test method, with the instrument being the dribbling test. The research analysis showed a significant effect of the two plyometric training between the results of the research sprint acceleration and two-leg skipping training on dribbling a football ball. There was a significant difference between the results of sprint acceleration training and two-leg skipping. It was concluded that the accelerated sprint and two-footed skipping methods could improve the ability to dribble the ball.